Sources of variation in reproductive traits of Bharat Merino sheep - DIXIT, S P; DHILLON, J S; SINGH, G (The Indian Journal of Animal Sciences, 2014)
The reproductive performance records of 661 Bharat Merino ewes spread over a period of 15 years from 1982 through 1996 were analysed by using the method of fitting constants. The least-squares means for the age at first conception, age at first lambing, service period, lambing interval, fertility rate and the annual reproduction rate were 580 ± 13 days, 730± 13 days, 142 ±26 days and 290 ± 26 days, 66 ± 3 % and 1.1 ± 0.0 respectively. The year, season, age and weight of the ewe were significant sources of variation in most of the reproductive traits. The estimates of heritability of the age at first conception and age at first lambing were 0.07 ± 0.13 and 0.12 ± 0.14, and those of repeatability for the fertility rate,service period and the lambing interval were 0.04 ± 0.01, 0.13 ± 0.02 and 0.13 ± 0.02 respectively. These estimates indicated that most of the variation in reproductive traits was due to temporary environmental conditions.